Mechanical performance of ITO/Ag/ITO multilayer films deposited on glass substrate by RF and DC magnetron sputtering. Issue 22 (15th November 2021) - Wang, Zhaoxin; Wang, Shunbo; Wang, Jiru; Niu, Yihan; Zong, Xiangyu; Li, Cong; Jiang, Shaodong; Zhao, Hongwei
Abstract: ITO/Ag/ITO multilayer thin films have been a potential substitute of the conventional single-layer transparent conducting film. Nevertheless, the mechanical stability under preparation and in-service conditions still limits their applications and developments. In this paper, the influences of different structural properties as well as layer structure on both surface morphological properties and mechanical properties of the ITO/Ag/ITO multilayer thin films in comparison with commercial single-layer ITO thin film were systematically investigated. The results demonstrate that, i) the tri-layer composite has large impacts on the preferential orientation, and exhibits the decreased values of surface roughness, net lattice distortion and residual stress; ii) the increased hardness ( H ) and decreased Young's modulus ( E ) for full annealed ITO/Ag/ITO multilayer films indicate that it is possible to tailor mechanical properties of the materials by manufacturing multilayer composite; iii) the ITO/Ag/ITO multilayer thin film exhibits remarkable improvements in wear resistance with the increase of annealing temperature, which is mainly attributed to the increased ratios of H / E and H 3 / E 2 .